Isolated myocardial relapse of Philadelphia-positive acute lymphoblastic leukaemia causing myocarditis: a case report. Issue 4 (26th September 2018) - Nadel, James; Meredith, Tom; Anthony, Chris; Sivasubramaniam, Vanathi; Jabbour, Andrew
Abstract: Background: Relapse of acute lymphoblastic leukaemia (ALL) causes significant morbidity. Extramedullary relapse is seldom isolated to one site and almost always coexists with extensive marrow disease. Leukaemic infiltration of the myocardium is a well described entity, evident in up to 44% of patients at post-mortem examination; however, ante-mortem diagnosis remains difficult and rare. As a result, myocardial involvement in the absence of any other foci of relapse has only seldom been reported. Case summary: Here, we present an unusual case of isolated gross intracardiac relapse of ALL in a patient presenting with chest pain and fevers. Both cardiac magnetic resonance imaging and endomyocardial biopsy were utilized in the diagnosis and identified leukaemic infiltrate in the absence of peripheral lymphoblasts. Discussion: Despite evidence supporting a positive correlation between peripheral lymphocyte count and myocardial infiltration, our case highlights the rare and hypothesis-driving occurrence of myocardial infiltration with a complete absence of a peripheral lymphoblastosis. The report highlights the utility of modern histopathological and imaging modalities in the diagnosis of isolated myocardial relapse of ALL and provides insight into the aetiologies driving this process.